DEVELOPMENT AND VALIDATION OF STABILITY INDICATING HPTLC METHOD FOR PIMAVANSERIN TARTRATE - DAMLE, MRINALINI C.; PARDESHI, ROSHANI R.; BIDKAR, SHUBHANGI R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The aim of current research work was to investigate degradation behavior of Pimavanserin tartrate upon exposure to stress conditions recommended by ICH Q1A (R2) and Q1B guidelines. Methods: Chromatographic separation was achieved on Merck’s TLC aluminum plates pre-coated with silica gel G 60 F254 as stationary phase and Methanol: Chloroform (2:8 v/v) as mobile phase. Densitometry scanning was carried out at 224 nm. Results: The retardation factor (Rf) was observed to be 0.56±0.02. Pimavanserin tartrate showed degradation in all stress conditions, but no degradation product was found in any stress condition. Peak purity was found to be 0.999 indicating no interference by degradation products to drug peak. The developed HPTLC method was successfully validated as per ICH Q2 (R1) guideline. Method was found to be linear within the range of 400-2000 ng/band with correlation coefficient R2= 0.9982. % RSD for intra-day and inter-day precision were found to be 1.35 and 1.78 % and % recovery was found to be in range 98-102 %. LOD and LOQ were found to be 17.58 ng/band and 53.27 ng/band respectively. Conclusion: A simple, economic stability indicating high performance thin layer chromatography method has been developed and validated for Pimavanserin tartrate. It is used for the treatment of delusions and hallucinations in Parkinson’s disease.